Ways to Create an Investment Mechanism for the Development of Cultural Tourism In Uzbekistan - Tohirov Dilyor (Universitas Muhammadiyah Sidoarjo, 2022)
The article highlights the importance of tourism in the economy of Uzbekistan, the objects of cultural heritage and the mechanisms of their use, provides theoretical, analytical analysis and assumptions about ways to invest in the implementation of these processes and their management.It also proves the importance of cultural tourism today and the effectiveness of the scheme of specific concepts and criteria for the restoration and investment of these resources.